The normative competence in the face of new political actors: a case study of telemedicine - Romão, Ana (Saúde e Sociedade, 2023)
The regulation of telemedicine in Brazil has been tortuous since its recognition by the Resolution No. 1,643/2002, of the Federal Council of Medicine (CFM), with issues regarding its competence to insert this practice. In 2018, the council issued a new resolution but it was revoked due to negative repercussions. The covid-19 pandemic put pressure on health services in such a way that the National Congress was pushed into conflict and enacted the Federal Law No. 13,989/2020, which allowed the practice of telemedicine during the period of health crisis. The article 6 of the law delegated the competence to regulate the post-pandemic practice to the CFM, further intensifying the discussions. This work is a case study on the regulation of telemedicine in Brazil, seeking to identify the legal conflicts imposed by the action of CFM in substitution of the Legislative Power. It uses the political model of implementation of public policies by William Clune as the basis for the analysis, using the qualitative documentary research method. In conclusion, the implementation of telemedicine must consider the political forces involved, understanding the CFM’s role in the normative process, to obtain, in the legal text, a public policy compatible with reality and capable of being implemented.